My bookstore : writers celebrate their favorite places to browse, read, and shop - Rice, Ronald; Parsons, Leif, 1975- (Black Dog & Leventhal Publishers : Distributed by Workman Pub. Co., 2012)
In this enthusiastic, heartfelt, and sometimes humorous ode to bookstores and booksellers, 84 well-known writers pay tribute to the bricks-and-mortar stores they love and often call their second home. Writers include: Isabel Allende, Wendell Berry, Rick Bragg, Dave Eggers, Louise Erdrich, Fannie Flagg, Ian Frazier, Henry Louis Gates, Jr., John Grisham, Pete Hamill, Ann Hood, Stephanie Kallos, Laurie R. King, Kate Niles, Ann Packer, Chuck Palahniuk, Ann Patchett, Francine Prose, Tom Robbins, Lisa See, Brian Selznick, Lee Smith, Nancy Thayer, Terry Tempest Williams and more.